A study on the sideband phenomenon of planetary gears - Kunihiko MORIKAWA; Kouji KUMAGAI; Ryuta NISHIHARA (Nihon Kikai Gakkai ronbunshu, 2014)
The mechanism of the sideband phenomenon of planetary gear vibration that often occurs in a planetary gear set was clarified in connection with mesh phase differences. This sideband phenomenon is one in which the (Z-1) or (Z+1) order component level is higher than the mesh order (Z) component level. The notation (Z-1) or (Z+1) means the mesh order (Z) minus or plus one carrier revolution. An in-phase (IP) planetary gear set has no such sideband phenomenon. In a sequentially phased (SP) planetary gear set, this phenomenon occurs in transverse and tilting vibration of sun gear, carrier and ring gear. Which sideband, either (Z-1) or (Z+1), occurs depends on the relationship between the mesh phasing direction and carrier rotation direction. To verify this sideband phenomenon, we derived the formulae to calculate the translational forces in x, y and z directions and the rotational moments about these translation axes which act to sun gear, carrier and ring gear due to mesh forces at each mesh point.